Social Media Influencers as “Dirty Workers”: An Explorative Study on How They Use Strategies to Reduce the Moral Taint - Claudia Gerhards (Social Media + Society)
Since social media influencers have become popular and monetize their content with the help of advertising deals, they have been associated with morally questionable, deceptive behavior. The list of misconduct is long. It includes, for example, not disclosing sponsored content, withholding negative experiences with promoted products, buying fake followers, and promoting false ideals of beauty. Building on the concept of “dirty work” as a theoretical framework, this article asks which strategies influencers use to soften this moral taint. Qualitative interviews with influencers living in Germany show that they are aware of their negative image in public and use various stigma management strategies. This article offers a perspective that has not yet played a role in the ethics debate about influencers. It asks how influencers, who are often associated with morally questionable practices, immunize themselves against this negative image and find a positive work identity.